Konsep Diri dan Optimisme Mahasiswa dalam Proses Penulisan Skripsi - Ryan Thanoesya; Syahniar Syahniar; Ifdil Ifdil (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2016)
Students who are likely to have a positive self concept will have a high sense of optimism in the process of thesis writting. This study aims to describe the concept of self-esteem and optimism the students in the process of thesis writting and identify relationships of self concept and optimism. This research is descriptive correlation with 61 students Guidance and Counseling as subject. This research used a questionnaire instrument and has passed the valid test. The research result reveal the condition of student self concept on category quite well and optimism of the student on good category, and there is a significant relationship between self concept and optimism of the student in the process of thesis writting by category. Necessary counseling services for optimizing student self concept and optimism.